2019
DOI: 10.1364/oe.27.009276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adapting luminance and CCT on appearance of white and degree of chromatic adaptation

Abstract: Past studies reported that the degree of chromatic adaptation was affected by viewing medium and adapting luminance. In this study, human observers adjusted the color appearance of a stimulus produced by a self-luminous display to make it appear as white as possible under different adapting conditions, whose adapting luminance and Correlated Color Temperature (CCT) levels were systematically varied. Though an identical display was used as the viewing medium, the chromaticities adjusted under the high adapting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 23 publications
13
25
0
Order By: Relevance
“…When the adapting condition was 9719 K, the chromaticities of the gray cube shifted toward a lower CCT. Such a trend of the chromaticity shift was very similar to those in past studies investigating the chromaticities for producing neutral colors (ie, white or gray) on displays 9,12,13,15,16 …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…When the adapting condition was 9719 K, the chromaticities of the gray cube shifted toward a lower CCT. Such a trend of the chromaticity shift was very similar to those in past studies investigating the chromaticities for producing neutral colors (ie, white or gray) on displays 9,12,13,15,16 …”
Section: Resultssupporting
confidence: 86%
“…Four adapting CCT levels (2856, 4500, 6500, and 9000 K) were designed. Our past experience suggested that a same adapting CCT would have very different appearances when using viewing booth and self‐luminous display, which was likely due to the incomplete chromatic adaptation caused by the viewing mode when viewing self‐luminous displays 13 . When viewing stimuli in the self‐luminous mode, the neutral colors at low CCT levels appear much chromatic (i.e., yellower).…”
Section: Preliminary Experimentssupporting
confidence: 75%
See 1 more Smart Citation
“…Both the MCDM values for the intraand inter-observer variations were comparable to those reported in several recent studies employing memory color matching. [15][16][17][18][19] 2.4.2 | Chromaticities of the adjusted stimuli Figure 3 shows the chromaticities of the reference stimuli and the average chromaticities of the adjusted stimuli in the CIE 1967 u 0 10 -v 0 10 chromaticity diagram. It can be observed that the average chromaticities that were adjusted under the higher L w were closer to the blackbody locus, suggesting the stimuli under a higher adapting luminance appeared less colorful.…”
Section: Inter-and Intra-observer Variationsmentioning
confidence: 99%
“…The magnitudes and ranges of the inter-and intra-observer variations were generally comparable to those in experiment 1 and past studies. [15][16][17][18][19] 3.3.2 | Chromaticities and color attributes of the adjusted stimuli Figure 8 shows the average chromaticities of the adjusted stimuli and the chromaticities of the reference stimuli in the CIE 1976 u 0 10 -v 0 10 chromaticity diagram; Figure 9 T A B L E 4 Colorimetric and photometric characteristics of the adapting conditions in experiment 2 shows the chromaticities of the adjusted stimuli in the a 0 10 -b 0 10 plane of CAM02-UCS, with the adapting luminance being included in the calculations. It can be observed that the chromaticities of the adjusted stimuli under the different adapting luminance levels were close to each other, as shown in Figure 9, which seems to illustrate that the CAM02-UCS can accurately predict the color matches.…”
Section: Inter-and Intra-observer Variationsmentioning
confidence: 99%